Effectiveness of Sambiloto (Andrographis paniculata) Supplementation on Antibody Titers of Newcastle Disease, Avian Influenza and Infectious Bursal Disease in Broilers - Hartono, Madi; Sirat, Muhammad Mirandy Pratama; Santosa, Purnama Edy; Ermawati, Ratna (Jurnal Sain Veteriner, 2024)
Newcastle Disease, Avian Influenza and Infectious Bursal Disease are three important broiler diseases with high morbidity and mortality that can increase broiler antibody titers. The aims of this study were to determine the effect and the best dose of immunomodulatory supplementation of Sambiloto (Andrographis paniculata) liquid extract by increasing the antibody titer of Newcastle Disease, Avian Influenza and Infectious Bursal Disease of broilers. The study was conducted for 30 days in the Karang Anyar broiler farm unit, Jati Agung District, South Lampung Regency, Lampung Province, experimentally five treatments and five repetitions for each treatment. Each repetition used five broilers. Five treatments with different doses, namely drinking water without liquid extract of Andrographis paniculata (P0); drinking water with liquid extract of A. paniculata 3 mg/kg BW (P1); 6 mg/kg BW (P2); 12 mg/kg BW (P3); (24 mg/kg BW (P4) 31-day-old broiler blood serum was obtained from the brachial vein using a 3 mL disposable syringe. Testing ND and AI antibody titers with HI test and IBD antibody titer with indirect ELISA test at MediLab Laboratory Antibody titer data in tabulation and analyzed descriptively. The content of andrographolide and flavonoids are thought to act as immunostimulants for specific and non-specific immune functions through the production of NK cells, macrophages, cytokine induction, IL-2 production, and lymphocyte proliferation. The conclusions of this study were supplementation of Sambiloto (Andrographis paniculata) liquid extract at a dose of 6 mg/kg BW in broiler drinking water could increase antibody titers against Newcastle Disease and Infectious Bursal Disease and at a dose of 24 mg/kg BW in broiler drinking water could increase antibody titres against Avian Influenza.